Digital Queue Prototype at West Denpasar Auxiliary Health Center - Agus Mahabojana Dwi Prayoga, Kadek; Dika Nugraha, Made; Gunantara, Nyoman (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2023)
In the growing era of digitalization, the use of technology is a solution to improve the efficiency of health services. Health centers often face the problem of long and irregular queues. A promising solution is the use of an Arduino Uno-based digital queue. This system allows patients to register electronically through a counter or mobile app. After registration, the patient is given a queue number which is displayed on the LCD screen. The advantage of this system is that it reduces patient waiting time, improves service efficiency, and helps medical staff manage queues better. This research aims to create an Arduino Uno-based digital queuing system at the Dauh Puri Sub-Community Health Center in West Denpasar. This tool consists of Arduino Uno, thermal printer, LCD display, speaker, and wireless push button at the counter. Testing shows that all devices are well integrated, providing timely responses. In conclusion, the Arduino Uno-based digital queue can improve efficiency and patient satisfaction at the health center.